The Role of Card Readers in the Conduct of 2019 General Elections in Gombe State: A Study of INEC Office, Gombe, Nigeria - Bello, Matthew Funsho; Hassan, Blessing Yanuti (Universitas Airlangga, 2025)
Abstract This study examined the effectiveness of smart card readers in ensuring credible electoral processes during the 2019 general elections in Gombe State, using the Independent National Electoral Commission (INEC) office as the unit of analysis. The research was guided by four specific objectives and one hypothesis. The target population comprised all 207 INEC staff members within the Gombe Local Government Area of Gombe State, from which a sample of 180 respondents was selected. Data for the study were obtained from both primary and secondary sources. The primary data were collected using a structured questionnaire, while the analysis employed descriptive statistics, arithmetic mean, and standard deviation. To test the hypothesis, the chi-square statistical method was applied. The results revealed a calculated chi-square value (x-cal) of 2.71, exceeding the tabulated chi-square value (x-tab) of 2.69 at the specified level of significance (p = 2.71 > 2.69), indicating a statistically significant outcome. The findings suggest that smart card readers contributed to the reliability of the 2019 general elections in Gombe State, Nigeria. Moreover, the study aligns with evidence from other countries where the adoption of smart card reader technology has enhanced electoral integrity. Consequently, the study recommends that residents of Gombe State—and Nigerians more broadly—adopt smart card readers across all tiers of electoral administration. Furthermore, it is advised that INEC and its ad hoc staff receive comprehensive training to address the operational challenges experienced during the 2019 elections. Keywords: Card reader, INEC Nigeria, Gombe state, Gombe local government, Nigerian 2019 general elections. Abstrak Penelitian ini mengkaji peran pembaca kartu (card reader) dalam memastikan keandalan pemilu pada Pemilu 2019 di Provinsi Gombe, dengan lokus kantor INEC sebagai unit analisis. Empat tujuan dan satu hipotesis dirumuskan untuk memandu penelitian ini. Populasi penelitian terdiri dari 207 pekerja INEC di Kabupaten Gombe, Provinsi Gombe, dengan sampel berjumlah 180 responden. Sumber data yang digunakan mencakup data primer dan sekunder. Data primer dikumpulkan melalui kuesioner, dan analisis dilakukan menggunakan statistik deskriptif, termasuk rata-rata aritmatika dan standart deviasi. Untuk menguji hipotesis, digunakan statistik inferensial berupa uji chi-square. Hasil penelitian menunjukkan nilai chi-square yang signifikan sebesar 2,71 (chi-square hitung, x-cal) dibandingkan dengan nilai chi-square tabel sebesar 2,69 (x-tab), dengan p = 2,71 > 2,69. Penelitian ini menyimpulkan bahwa penggunaan pembaca kartu (smart card reader) berkontribusi pada keandalan Pemilu 2019 di Provinsi Gombe, Nigeria. Selain itu, penelitian ini menunjukkan bahwa beberapa negara telah mengalami peningkatan signifikan dalam proses pemilu setelah mengadopsi teknologi pembaca kartu pintar. Penelitian ini merekomendasikan agar masyarakat Provinsi Gombe, dan warga Nigeria pada umumnya, mengadopsi pembaca kartu pintar untuk semua tingkat administrasi pemilu. Selain itu, untuk mengatasi tantangan yang dihadapi selama Pemilu 2019, disarankan agar INEC dan staf ad hoc menerima pelatihan yang memadai dalam penggunaan pembaca kartu pintar. Kata kunci: Pembaca kartu, INEC Nigeria, Negara Bagian Gombe, pemerintah lokal Gombe, Pemilu Nigeria 2019.